Resorcinol - determination method in the workplace air - Anna Jeżewska; Dorota Kondej (Nofer Institute of Occupational Medicine, 2022)
Background Resorcinol (1,3-dihydroxybenzene) is a white solid used in rubber, pharmaceuticals, cosmetics, paints and varnishes and other industries. Resorcinol is a harmful, irritant, methemoglobin-forming and hemolytic substance. It can cause kidney and liver damage. The aim of the study was to develop a method for the determination of resorcinol in the workplace air, which would enable the determination of its concentrations in the range 0.1-2 of the MAC (maximum allowable concentration) value. Material and Methods The method relies on passing the test air containing resorcinol through a cellulose filter, extraction with aqueous methanol solution and chromatographic analysis of the obtained solution. The tests were performed using a liquid chromatograph (HPLC) 1200 series of Agilent Technologies with a diode array detector (DAD). The determinations were carried out using an Allure Basix column (250 × 4.6 mm, 5 μm granulation). The procedure was validated according to European Standard PN-EN 482. Results The developed method allows the determination of resorcinol in the workplace air in the concentration range of 4.5-90 mg/m 3 . The limit of detection is 0.087 μg/ml, the precision 5.16% and the relative expanded uncertainty 22.6%. The method described enables selective determination of resorcinol in workplace air in the presence of 1,2-dihydroxybenzene, 1,4-dihydroxybenzene, benzene and phenol. Conclusions The method is characterized by good precision and accuracy; it meets the requirements of the European Standard PN-EN 482, and can be used by occupational hygiene laboratories to measure concentrations of resorcinol in workplace air to assess workers' exposure to this substance. Med Pr. 2022;73(2):135-42